2002
DOI: 10.1021/ma011402+
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separation of Ultrahigh Molecular Weight Isotactic Polypropylene Solutions in the Gelation Process Estimated in Relation to the Morphology and Mechanical Properties of the Resultant Dry Gel Films

Abstract: The phase separation of ultrahigh molecular weight isotactic polypropylene (it-UHMWPP) solution in the gelation process was investigated by quenching the solutions to the desired temperature. When an incident beam of an He−Ne gas laser was directed to the gel, the logarithm of scattered intensity increased linearly with time in the initial stage and tend to deviate from this linear relationship in the later stage. The melting endotherm of the differential scanning calorimetry curve showed a clear peak in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 36 publications
2
23
1
Order By: Relevance
“…The spectra of the irradiated samples were obtained near the surface and at a depth near the Bragg peak. The spectra show distinct absorption peaks at 973 and 899 cm À 1 , corresponding to rocking of the CH 3 coupled with stretching of the C-C in the helical sequences of $5 units in length in iPP chain, and rocking of the CH 3 coupled with rocking of the CH 2 in the shorter sequences in iPP chain, respectively (Miyazawa et al, 1963;Bayer et al, 1980;Matsuo et al, 2002;Kang et al, 2010). Both of the peaks significantly decrease in intensity near the surface on irradiation of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…The spectra of the irradiated samples were obtained near the surface and at a depth near the Bragg peak. The spectra show distinct absorption peaks at 973 and 899 cm À 1 , corresponding to rocking of the CH 3 coupled with stretching of the C-C in the helical sequences of $5 units in length in iPP chain, and rocking of the CH 3 coupled with rocking of the CH 2 in the shorter sequences in iPP chain, respectively (Miyazawa et al, 1963;Bayer et al, 1980;Matsuo et al, 2002;Kang et al, 2010). Both of the peaks significantly decrease in intensity near the surface on irradiation of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, more detailed analysis has been reported for several kinds of polymer. By using successful analysis of the linear theory of spinodal decomposition by Cahn [9,10], Matsuo et al extended to some crystalline polymer solutions such as PVA [11,12], polypropylene [13], agarose [14,15], and polyethylene [16] in order to investigate whether the gelation by the quenching is attributed to the phase separation of solution by the concentration fluctuation.…”
Section: Introductionmentioning
confidence: 99%
“…Further detailed studies have been carried out by Matsuo et al for UHMWPP [13] based on light-scattering, X-ray, infrared, and Raman measurements. Through a series of experimental results, Matsuo et al provided conclusive evidence that when crystalline polymer solutions are quenched, the liquid-liquid phase separation associated with spinodal decomposition occurs at first and the crystallization occurs subsequently in the polymer-rich phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gelation of a crystalline polymer such as isotactic polypropylene (iPP) is closely associated with the formation of crystal as a cross-linking point. [1][2][3][4][5] Okabe et al reported a solgel transition and the morphology of iPP gel by thermal analysis and polarizing microscopy, 6,7 and found that the gel melting temperature is fitted as a function of polymer concentration by a Eldridge-Ferry plot and many spherulites exist in the gel. There exist three types of crystalline modification.…”
mentioning
confidence: 99%